ANALISIS TINGKAT BUNGA KREDIT SEPEDA MOTOR DI KOTA MADIUN - Desanto W., Rino (Widya Warta, 2017)
The motorcycle market offers payment by credit for the customers with different amount of money for the down payment, the installment payment and the period of installment payment. However, the customers do not get clear information about how much interest rate they should pay. This research was conducted to find the interest rates on motorcycle loans in Madiun. The method applied in this research was by calculating the interest rates on motorcycle loans in Madiun. The data were taken from the motorcycle credit list brochures given by the dealer, in which each brand of motorcycle was represented by one brochure. Moreover, they provided the lowest price, highest price and midle price for installment payment of one month, two months and three years. Based on the calcualtion of interest credit rate, the average of the loan interest rates were quite high. Kawasaki motorcycle had the average of loan interest rates which were lower than many other motorcycles with different brands. The other four motorcycles, the highest of the loan interest rate comes to the loan with the lowest installment payment of one year. The longer payment period the lower of credit interest will be. The dealer was supposed to give better information about the offered loan interest rate so that people had many choiches in deciding what motorcycles they would buy wether in cash or credit.